2013
DOI: 10.1159/000346158
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 Expression in Glia and Neurons Alters in Response to White Matter Injury in Preterm Infants

Abstract: Toll-like receptors (TLRs) are members of the pattern recognition receptor family that detect components of foreign pathogens or endogenous molecules released in response to injury. Recent studies demonstrate that TLRs also have a functional role in regulating neuronal proliferation in the developing brain. This study investigated cellular expression of TLR3 using immunohistochemistry on human brain tissue. The tissue sections analysed contained anterior and lateral periventricular white matter from the fronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 32 publications
(44 reference statements)
1
46
0
Order By: Relevance
“…with Poly I:C alters fetal brain development in an IL-6-dependent manner (Smith et al, 2007). However, in our experiments, the findings are correlative, and additional studies, using for example relevant knock-out animals or cytokine stimulation in TRIF KO mice, are needed to determine the specific roles of these inflammatory mediators in TLR-3-induced brain injury.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…with Poly I:C alters fetal brain development in an IL-6-dependent manner (Smith et al, 2007). However, in our experiments, the findings are correlative, and additional studies, using for example relevant knock-out animals or cytokine stimulation in TRIF KO mice, are needed to determine the specific roles of these inflammatory mediators in TLR-3-induced brain injury.…”
Section: Discussionmentioning
confidence: 61%
“…The direct influence of IL-6 on the development of brain injury is more controversial. Although studies have consistently demonstrated elevated IL-6 levels in asphyxiated infants (Sävman et al, 1998) and mice overexpressing IL-6 develop severe neurologic syndromes (Campbell et al, 1997), others find that mice deficient in IL-6 develop more severe brain injuries (Penkowa and Hidalgo, 2000). Interestingly, maternal immune activation ϩhigh -expressing and a CD11b ϩlow -expressing population, which were both affected by HI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing TLR activation on immune cells is associated with increased immune cell infiltrates, microglial activation and cytokine release (Cai et al, 2000). It is suggested that, in particular, TLR3 protein expression in the brain is upregulated in cases of white matter injury and invading pathogens in the preterm brain (Vontell et al, 2013). TLR3 is implicated in normal neural cell differentiation and proliferation.…”
Section: Experimental Animal Models To Examine Chorioamnionitismentioning
confidence: 99%